The mitochondrial phylogeography of the Crimean endemic lizard Darevskia lindholmi (Sauria, Lacertidae): Hidden diversity in an isolated mountain system - Oleg Kukushkin; Oleg Ermakov; Iulian Gherghel; Svetlana Lukonina; Anton Svinin; Igor Doronin; Evgeniy Simonov; Daniel Jablonski (Vertebrate Zoology, 2021)
Abstract The Lindholm rock lizard, Darevskia lindholmi, is the only member of the genus Darevskia whose range is restricted solely to Europe, representing a local endemism found only in the Crimean Mountains. In our study, we investigated the cytochrome b gene (mtDNA) of 101 D. lindholmi sequences from 65 Crimean localities, representing its entire range. We found that D. lindholmi is highly genetically structured, and its range is divided into populations belonging to three mitochondrial lineages. The Lindholm rock lizard populations inhabiting the middle part of the Crimean Mountains (further referred to as the Central lineage) are sharply differentiated from the other two lineages (the Common and the Southwestern lineages), which are present in most of the species range. The genetic distance between the Central lineage and the other two taken together is 4.6%, according to our results, suggesting that the divergence occurred during the Early Pleistocene. The narrowly distributed Southwestern lineage and the widespread Common lineage, on the other hand, are differentiated by 1%. Field observations on the representatives of the main evolutionary groups show that their ecology is also different: the Central lineage is a mesophilic and cold-resistant form, while the other two closely related lineages are more xerophilic and thermophilic. Results of the potential ranges modeling and ecological niche analysis confirm that the genetic lineages occupy different niches of the Crimea. Furthermore, the area of inhabitation of the Central lineage splits the western and eastern parts of the Common lineage range, while the Southwestern lineage is restricted along the coast of the southwestern coast of the peninsula. The long-term co-existence of deeply divergent sister mitochondrial lineages in a relatively small (circa 7,000 km2) isolated mountain system serves as a mesocosm for understanding the speciation process. Our data suggest that the Central lineage warrants further taxonomic investigation.